Surfactant Free, Non-aqueous Method, for the Deposition of ZnO Nanoparticle Thin Films on Si(100) Substrate with Tunable Ultraviolet (UV) Emission - Brahma, Sanjaya; Shivashankar, S.A. (Current Nanoscience, 2013)
We report, strong ultraviolet (UV) emission from ZnO nanoparticle thin film obtained by a green synthesis, where the film is formed by the microwave irradiation of the alcohol solution of the precursor. The deposition is carried out in non-aqueous medium without the use of any surfactant, and the film formation is quick (5 min). The film is uniform comprising of mono-disperse nanoparticles having a narrow size distribution (15-22 nm), and that cover over an entire area (625 mm2) of the substrate. The growth rate is comparatively high (30-70 nm/min). It is possible to tune the morphology of the films and the UV emission by varying the process parameters. The growth mechanism is discussed precisely and schematic of the growth process is provided.
Keywords: optical properties